2017
DOI: 10.1136/bjophthalmol-2017-310700
|View full text |Cite
|
Sign up to set email alerts
|

Identification of imaging features that determine quality and repeatability of retinal capillary plexus density measurements in OCT angiography

Abstract: Our study identified the imaging parameters that determined the repeatability of quantitative retinal vessel density measurements. These findings have implications in determining if OCT-A images can be used to accurately evaluate serial changes in retinal vessel density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 32 publications
5
55
0
Order By: Relevance
“…Our results are consistent with literature reports on the OCTA metrics for macular superficial capillary 29. The high repeatability suggests that the moderate interocular correlation of fractal dimension and VDI and poor interocular correlation of the parafoveal vessel density are not due to variation in measurements.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with literature reports on the OCTA metrics for macular superficial capillary 29. The high repeatability suggests that the moderate interocular correlation of fractal dimension and VDI and poor interocular correlation of the parafoveal vessel density are not due to variation in measurements.…”
Section: Discussionsupporting
confidence: 92%
“…In a similar study to ours, Oh et al assessed in 261 Asian individuals, the relationship between retinal and choroidal VD, and concluded that CC VD varies with retinal VD (SCP VD vs CC VD R = .278, DCP VD vs CC VD R = .273; both P < .001) rather than with choroid structure (VD vs subfoveal choroidal thickness R = .100; P = .109). 34,35 These variation sources will need to be addressed before OCTA can be used in routine clinical practice for the diagnosis and management of retinal diseases. As stated by Rabiolo et al, it should be highlighted that absolute VD values calculated with different algorithms are not directly interchangeable, so studies adopting VD as an outcome measure should not rely on external normative databases.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Also, numerous other variables such as measurement and analysis methods, motion artefacts or diurnal variations may affect the accuracy and repeatability of VD measurements. 34,35 These variation sources will need to be addressed before OCTA can be used in routine clinical practice for the diagnosis and management of retinal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Fenner et al. () reported that the visibility of the fine vasculature of the retinal capillary plexus, motion artefacts and the TopQ score, which represents similar parameters to SS, could be used to assess the quality of OCTA scans to ensure reliability. As we excluded images with any artefacts, both studies are consistent in the importance of SS in terms of OCTA reliability.…”
Section: Discussionmentioning
confidence: 99%
“…, ; Fenner et al. ). These OCTA parameters also showed reasonable repeatability in patients with various ophthalmic diseases in other studies (Lee et al.…”
Section: Introductionmentioning
confidence: 99%